2017
DOI: 10.1080/02770903.2017.1296157
|View full text |Cite
|
Sign up to set email alerts
|

Novel monoclonal treatments in severe asthma

Abstract: Research on the biological treatment of asthma shows promising results. While anti-IgE (omalizumab) has been used in the treatment of asthma for some years, anti-IL-5 has recently been approved for use. The efficacy of results of other large studies with a longer duration is needed to draw a firm conclusion. Such studies should not only focus on clinical outcomes, but also consider asthma-related quality of life. Knowledge on the asthma phenotypes and identification of biomarkers associated with these will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…If we look at the human clinical studies for emerging monoclonal antibodies in treating asthma for the past 20 years, studies targeting IgE, IL-2, IL4R-alpha, IL-5, and IL-13 showed some efficacy, however those targeting TNF-alpha, TSLP and IL-9 did not show convincing effectiveness [38] and no asthma clinical trials targeting IL-6 have been conducted to the best of our knowledge. It is likely that TNF-alpha and IL-6 may not be the culprits of allergic airway inflammation and may be merely one of the biomarkers participating the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…If we look at the human clinical studies for emerging monoclonal antibodies in treating asthma for the past 20 years, studies targeting IgE, IL-2, IL4R-alpha, IL-5, and IL-13 showed some efficacy, however those targeting TNF-alpha, TSLP and IL-9 did not show convincing effectiveness [38] and no asthma clinical trials targeting IL-6 have been conducted to the best of our knowledge. It is likely that TNF-alpha and IL-6 may not be the culprits of allergic airway inflammation and may be merely one of the biomarkers participating the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…9 Key in the IL-4/IL-13 axis is the IL-4Rα signaling which has been identified as a potential target for asthma therapies. [12][13][14] Deficiency of IL-4Rα in allergen-sensitized mice shows reduced allergen-induced symptoms such as AHR, eosinophilia, and mucus hyperplasia in vivo. [15][16][17] We and others have also illustrated various cell-specific roles of IL-4Rα signaling during the development of allergic disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Key in the IL‐4/IL‐13 axis is the IL‐4Rα signaling which has been identified as a potential target for asthma therapies . Deficiency of IL‐4Rα in allergen‐sensitized mice shows reduced allergen‐induced symptoms such as AHR, eosinophilia, and mucus hyperplasia in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of severe asthma, it is certainly promising to see the recent development and subsequent licensing of several novel treatments [3]. Indeed, within the past year, a number of biologic agents (e.g.…”
mentioning
confidence: 99%
“…Indeed, within the past year, a number of biologic agents (e.g. Mepolizumab and Reslizumab) have become available, targeting a Type-2 inflammatory pattern [3][4][5]. These therapies certainly considerably advance the available treatment options in severe asthma and indeed for many individuals will be transformational.…”
mentioning
confidence: 99%